IgY-technology (egg yolk antibodies) in human medicine: a review of patents and clinical trials - Leiva, Carlos (2020)
IgY-technology (the production and extraction of specific IgY antibodies from egg yolk) is an innovative method to produce antibodies for therapy and prophylaxis. Advantages of IgY over other antibodies comprise its cost-effective extraction, the minimization of animal harm and distress, and its reduced reactivity with mammalian factors. Many research groups have demonstrated that IgY is active against several pathogens or conditions, a fact that may support the design of novel, safe and effective health products. This review provides a comprehensive analysis of IgY-based biologicals for human medicine, including patent applications and clinical trials during the period 2010–2018, and addresses how IgY-technology can lead to innovation in the production of biologicals for the treatment and prophylaxis of a wide range of infectious and non-communicable diseases.